Observation of $B^+_c → J/ψD_s^+$ and $B^+_c → J/ψD_s^{*+}$ decays - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
The decays $B^+_c \rightarrow J/\psi D_s^+$ and $B^+_c \rightarrow J/\psi D_s^{*+}$ are observed for the first time using a dataset, corresponding to an integrated luminosity of 3$fb^{-1}$, collected by the LHCb experiment in proton-proton collisions at centre-of-mass energies of $\sqrt{s}$=7 and 8 TeV. The statistical significance for both signals is in excess of 9 standard deviations. The following ratios of branching fractions are measured to be $BR(B^+_c \rightarrow J/\psi D_s^+)/BR(B^+_c \rightarrow J/\psi \pi+) = 2.90 \pm 0.57 \pm 0.24$, $BR(B^+_c \rightarrow J/\psi D_s^{*+}) / BR (B^+_c \rightarrow J/\psi D_s^+) = 2.37 \pm 0.56 \pm 0.10$, where the first uncertainties are statistical and the second systematic. The mass of the \Bc meson is measured to be $m_{B^+_c} = 6276.28 \pm 1.44 (stat) \pm 0.36(syst) MeV/c^2$, using the $B^+_c \rightarrow J/\psi D_s^+$ decay mode.